Occupational therapy in HomEcare Re-ablement Services (OTHERS): study protocol for a randomized controlled trial - Whitehead, Phillip J.; Drummond, Avril E.R.; Walker, Marion F.; Parry, Ruth H.; McGeorge, Ian D.; Latif, Zaid (BioMed Central, 2014)
Background: Homecare re-ablement services have been developed by local authorities in England in response to the government agenda for health and social care. These services aim to optimize users’ independence and ability to cope at home, and reduce the need for ongoing health and social care services. However, there is currently limited evidence and guidance regarding the optimum configuration and delivery of re-ablement services. In particular, the impact of occupational therapy input on service user outcomes has been highlighted as a specific research priority. Methods/Design: This feasibility randomized controlled trial (RCT) will recruit 50 people from one local authority led homecare re-ablement service in England. Those who provide informed consent will be randomized to receive either usual homecare re-ablement (without routine occupational therapy input) or usual homecare re-ablement plus an enhanced program targeted at activities of daily living (ADL), delivered by an occupational therapist. The primary aim of this study is to assess the feasibility of conducting a further, powered study. The participant outcomes assessed will be independence in personal and extended ADL, health and social care-related quality of life, number of care support hours, falls, acute and residential admissions and use of health and social care services. These will be assessed at two weeks, three months and six months post-discharge from the re-ablement service. Discussion: To our knowledge, this is the first RCT of occupational therapy in homecare re-ablement services. The results of this study will lay the foundations for a further powered study. The findings will be relevant to researchers, clinicians, commissioners and users of adult social care services.